Examining Prevalence, the Relationship of Neurotransmitters Associated with Happiness, Stress, Leadership, Motivation, and Organizational Reciprocal Trust - Shahzadi, Shazia; Juhary, Ali; Asghar, Umair; Munir, Naureen; Shah, Syed Shoaib; Farooque, Muhammad Anees (2024)
This article delves into the intricate interplay between our body's chemical responses and their impact on the organizational environment, particularly focusing on the neurotransmitters associated with stress and happiness: dopamine (often referred to as the motivation hormone), serotonin (commonly known as the mood regulator), and oxytocin (recognized as the trust hormone). It examines how these chemicals influence the level of trust that Pakistani workers place in their leadership. The significance of studying the chemical dynamics of happiness within organizational settings stems from their multifaceted roles, particularly in decision-making processes, which are pivotal for task execution. Specifically, the exploration of oxytocin, triggered by positive emotions through the chemical pathways of happiness, or conversely, by elevated levels of cortisol resulting from stress, is deemed essential in preempting adverse outcomes that impact mental well-being, organizational culture, and climate. Such outcomes encompass conflicts among employees, compromised cognitive capabilities, reduced creativity and problem-solving skills, leading to demotivated workforce and, often, high turnover rates. To delve into this topic, the research methodology employed comprises qualitative exploratory research and literature review. These approaches, coupled with data collection, aim to fulfill the objectives outlined in this article.